There is more than just longitudinal strain: prognostic significance of biventricular circumferential mechanics. (3rd October 2022) - Fabian, A; Tolvaj, M; Lakatos, B K; Assabiny, A; Ujvari, A; Shiida, K; Ferencz, A; Schwertner, W; Veres, B; Kosztin, A; Staub, L; Sax, B; et al.
Abstract:  : Global longitudinal strain is a well-established predictive parameter of adverse outcomes in several cardiac diseases, therefore, it is widely used in clinical practice. Despite the significant contribution of circumferential shortening to the global ventricular function, data are scarce concerning the biventricular circumferential strain phenotypes and their prognostic value on long-term mortality. Accordingly, the aim of our study was to assess both left (LV) and right ventricular (RV) global circumferential strain (GCS) using 3D echocardiography in order to determine the prognostic importance of the deterioration of biventricular circumferential mechanics. Three hundred and sixty-four patients with various established left-sided heart diseases were retrospectively identified (age: 64.8±15.0 years, 69% males) with a median follow-up of 41 months. All patients underwent clinically indicated transthoracic echocardiography and left (LV) and right ventricular (RV) ejection fractions (EF) were measured by 3D analysis. 3D LV and RV GCS were also quantified by dedicated softwares. In order to determine the prognostic power of the different patterns of biventricular circumferential mechanics, we divided the patient population into four groups using the median values of LV and RV GCS (absolute values of 27.1% and 17.9%, respectively). Group 1 consisted of patients with both LV and RV GCS above median values; Group 2 was defined as patients with LV GCS above the median, while RV GCS below the median, whereas in Group 3 patients had LV GCS values below the median, while RV GCS was above median. Group 4 was defined as patients with both LV and RV GCS below the median. The primary endpoint of our study was all-cause mortality. Fifty-five patients (15.1%) met the primary endpoint. The overall patient population showed balanced values of LV and RV EF (49.0±15.7 and 48.2±9.4%, respectively). Comparing the population separated into the above-mentioned four groups based on LV and RV GCS values enabled a detailed risk stratification as shown on the Kaplan-Meier curve (Figure 1.) When comparing Group 1 vs. Group 4, patients who had lower LV and RV GCS values the risk of all-cause mortality was more than 5 times higher than in patients with both LV and RV GCS above the median (HR, 5.240 [95% CI, 2.750–9.985], p<0.001). By comparing Group 2 with Group 3, the associated risks for all-cause mortality did not show a difference (HR, 0.461 [95% CI, 0.178 to 1.194], p=NS) as shown on the Kapan-Meier curve (Figure 2). Based on the different phenotypes of LV and RV GCS, decreased biventricular circumferential shortening was associated with a significantly increased risk of long-term all-cause mortality. Interestingly, decreased RV GCS with maintained LV GCS showed a similar risk of adverse outcomes than decreased LV GCS with maintained RV GCS. Our results emphasize the importance of the assessment of biventricular circumferential mechanics. Funding Acknowledgement: Type of funding sources: None.